Ancient Tsunami Records in the Viscous Remanent Magnetization of Reworked Boulders in the Kingdom of Tonga - Sato, Tetsuro; Nakamura, Norihiro; Sato, Masahiko; Kato, Chie; Goto, Kazuhisa; Watanabe, Masashi; Satake, Kenji; Kula, Taaniela (Geophysical research letters, 2024)
The movement history of boulders is crucial for the reconstruction of paleo‐tsunamis. We report findings from viscous remanent magnetization studies of the boulders on Tongatapu Island, aiming to reconstruct their reworkings. Two boulders exhibited viscous remanence, whereas two larger boulders lacked viscous components but exhibited stable remanence. Both the viscous and stable components deviated from the geomagnetic field direction. These observations indicate that: (a) the boulders with a viscous component were reworked before the latest event, which could have reworked all boulders, and (b) the magnitude of the latest event was larger than that of an earlier event. The reworked timing indicated that the event occurred between 3,000 years ago and the fifteenth century. The difference in the wave height required to move boulders on the eastern and western coasts suggests that the source of the earlier tsunami was likely an eruption due to volcanoes along the Tonga Ridge. Plain Language Summary This study explores prehistoric tsunamis on Tongatapu Island by examining large rocks transported during the past tsunamis. Upon analyzing the magnetic records of the rocks, we discovered evidence of multiple rock movements, shedding light on the recurrence and magnitude of past events. Magnetic measurements and previously dated latest movement ages revealed that a tsunami occurred between 3,000 years ago and the fifteenth century. Considering the mobility and immobility of the large rocks and their sizes, the data suggest a smaller paleo‐tsunami magnitude than that of the fifteenth‐century event that transported all the rocks; this expands our understanding of natural hazard history and has implications for assessing tsunami risks in the region. The approach adopted here provides a valuable model for investigating historical natural disasters and their impact on coastal areas, offering insights to enhance global tsunami hazard assessment strategies. Key Points Viscous remanent magnetization of large boulders indicates multiple reworkings, enhancing our understanding of past tsunamis in Tongatapu Combined magnetic records and published radiocarbon ages suggest tsunamis occurred between 3,000 years ago and the fifteenth century Remanence and wave height estimates show that the older tsunami was smaller than the fifteenth‐century event, with a possible volcanic source